Pati Resistan serta Perannya dalam Penghambatan Proliferasi dan Induksi Apoptosis Sel Kanker Kolon - PURWANI, ENDANG YULI (Indonesian Journal of Cancer, 2014)
Resistant starch (RS) is starch fraction which is not digested by human starch degrading enzyme, and it will thus undergo bacterial fermentation in the colon. The main fermentation products are Short Chain Fatty Acid (SCFA): acetate, propionate and butyrate. The Fermentation products were able to inhibit the proliferation and to induce apoptosis of colon cancer cell. The apoptosis occured through mitochondrial pathway by changing the expression of pro-apoptosis related gene of Bax toward antiapoptosis related gene of Bcl-2.